2001
DOI: 10.4049/jimmunol.167.12.7169
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of T and B Lymphocyte Activation in Nonobese Diabetic Mice

Abstract: Type 1 diabetes in nonobese diabetic (NOD) mice is characterized by the infiltration of T and B cells into pancreatic islets. T cells bearing the TCR Vβ3 chain are disproportionately represented in the earliest stages of islet infiltration (insulitis) despite clonal deletion of most Vβ3+ immature thymocytes by the mammary tumor virus-3 (Mtv-3) superantigen (SAg). In this report we showed that a high frequency of NOD Vβ3+ T cells that escape deletion are activated in vivo and that this phenotype is linked to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 102 publications
(79 reference statements)
1
15
0
Order By: Relevance
“…Macrophages are not capable of naive T cell priming and most likely have a role in the amplification of autoreactive T cell responses, particularly given their high IL-12 production. One possible interpretation of our findings is that B cells and macrophages possess a functional advantage among NOD professional APC owing to their aberrantly activated state in the periphery (71) and their hyperactivity during maturation (13,14), whereas DC are resting in the steady-state and possess a largely normal ability to activate T cells. Importantly, however, the fact that the presentation of NOD DC defects is context-dependent suggests that the relevance of APC functional defects to autoimmunity will depend upon the maturation signals and the local APC composition.…”
Section: Discussionmentioning
confidence: 83%
“…Macrophages are not capable of naive T cell priming and most likely have a role in the amplification of autoreactive T cell responses, particularly given their high IL-12 production. One possible interpretation of our findings is that B cells and macrophages possess a functional advantage among NOD professional APC owing to their aberrantly activated state in the periphery (71) and their hyperactivity during maturation (13,14), whereas DC are resting in the steady-state and possess a largely normal ability to activate T cells. Importantly, however, the fact that the presentation of NOD DC defects is context-dependent suggests that the relevance of APC functional defects to autoimmunity will depend upon the maturation signals and the local APC composition.…”
Section: Discussionmentioning
confidence: 83%
“…Unmanipulated NOD mice have a higher frequency of activated B cells compared to non diabetes-prone strains of mice [68]. This was indicated by a higher frequency of CD69 + B220 + B cells in mice as young as 14 days of age.…”
Section: B Cell Characteristics In Nod Micementioning
confidence: 76%
“…This was indicated by a higher frequency of CD69 + B220 + B cells in mice as young as 14 days of age. The CD69 + B cells showed an increase in the level of MHC class II, and the costimulatory molecules B7.1 and B7.2 [68]. It was suggested, by comparison of H-2 g7 -expressing mouse strains with non-H-2 g7 strains that the activated phenotype was correlated with the H-2 haplotype.…”
Section: B Cell Characteristics In Nod Micementioning
confidence: 87%
See 1 more Smart Citation
“…Our current findings illustrate that the Glp1r is more widely expressed in immune subpopulations from the NOD, relative to the C57BL/6 background. Chiu et al demonstrated a higher frequency of activated B and T cells in the NOD mouse compared with other strains, including the C57BL/6 mouse [31]. Hence one potential explanation for the differential Glp1r expression could be the activation status of lymphocytes, as we did not discriminate between rested and activated B and T cells during the sorting procedure.…”
Section: And 5)mentioning
confidence: 99%